Molecular identification and nutritional analysis of green tide algae in the coastal waters of Qinhuangdao, China - Li, Yan; Ma, Xiaojun; Jiang, Meijie; Song, Wei; Wang, Gang; Han, Hongbin (Frontiers in Marine Science, 2023)
Since 2015, the coastal waters of Qinhuangdao in Hebei province, China have experienced green tide disasters for consecutive years. Resource utilization is an important measure for preventing and controlling green tides. To comprehensively utilize green tide algae, this study first identified theses green tide algae and then assessed their nutritional value. Based on analysis of the internal transcribed spacer (ITS), 5S spacer regions (5S) and the mitochondrial cytochrome C oxidase I (COI), the dominant species were Ulva prolifera, Bryopsis plumose, Ulva australis, and Gracilariopsis lemaneiformis. The basic nutritional components, i.e., chlorophyll, amino acids, mineral elements, and heavy metal contents, of these four algae were measured and analyzed, and the four dominant species were shown to be high-nutrient-value marine foods with complete and reasonable protein, amino acid, and mineral compositions. This indicates that there is value in further research and development towards their utilization as nutrient sources. This study provides a basis for the comprehensive development and utilization of green tide algae resources in the coastal waters of Qinhuangdao.